Patient‐Reported Continuity of GLP‐1 Receptor Agonist Therapy - You Chen; Gracie Piantek; Xinmeng Zhang; Yubo Feng; Chao Yan; Jason M. Samuels; S. Trent Rosenbloom; Danxia Yu; Laurie L. Novak; Gitanjali Srivastava (Obesity Science & Practice, 2026)
ABSTRACT Objective Use of GLP‐1 receptor agonists is associated with significant weight loss in many individuals. Discontinuation is associated with weight regain. Patients' experience with this is not well characterized. This study describes the patient experience of continuity of care. Methods A cross‐sectional electronic survey was administered to adults identified from an academic medical center's electronic health records as having at least one GLP‐1 RA prescription in the preceding 6 years and a subsequent prescription gap of greater than 90 days. The 87‐item instrument spanned six domains: care settings, comorbidity and treatment context, continuity, discontinuity, dietitian/lifestyle support, and digital‐feature preferences. Primary outcomes were item‐level frequencies. Exploratory composites included a 7‐item Continuity‐of‐Care Index (CCI) and a 5‐item Discontinuity Index (DIS), each rescaled 0–100; subgroup comparisons used Kruskal–Wallis, Mann‐Whitney, and chi‐square tests, with multiple‐imputation sensitivity analyses. Results Of 4890 invitations, 261 adults completed the survey (5.3%); 143 (54.8%) reported current use of a prescription weight‐management medication and 159 (60.9%) reported prior‐authorization requirements. Among them, 79 (49.7%) either waited more than 7 days or were never approved. Continuity strengths included knowing whom to contact about medications (76.2%) and timely team responses (70.7%); the weakest items were cross‐clinic coordination (54.1%) and visibility into required next steps (52.2%). The CCI (mean 69.5 [SD 22.7]; α = 0.90; n = 242) varied by most‐visited clinic (Kruskal–Wallis p < 0.001), highest at the weight‐management clinic (median 82.1) and lower at primary care (60.7). Among current medication users, 32.4% reported a ≥ 14‐day medication gap. The most desired digital features were all‐in‐one tracking of refills, prior authorization, and appointments (89.5%) and real‐time prior‐authorization status (87.2%). Conclusions Patients described obesity‐care disruptions primarily as process failures, including prior authorization delay, out‐of‐pocket cost, pharmacy stock‐outs and dispensing delays, and fragmented cross‐clinic coordination. They prioritized transparent, workflow‐oriented navigation.